Design and Development of Stream Processor Architecture for GPU Application Using Reconfigurable Computing - Sanket Dessai; Krishna Bhushan Vutukuru (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
Graphical Processing Units (GPUs) have become an integral part of today’s mainstream computing systems. They are also being used as reprogrammable General Purpose GPUs (GP-GPUs) to perform complex scientific computations. Reconfigurability is an attractive approach to embedded systems allowing hardware level modification. Hence, there is a high demand for GPU designs based on reconfigurable hardware. Stream processor consists of clusters of functional units which provide a bandwidth hierarchy, supporting hundreds of arithmetic units. The arithmetic cluster units are designed to exploit instruction level parallelism and subword parallelism within a cluster and data parallelism across the clusters.For decreasing the area and power, a single controller is used to control data flow between clusters and between host processor and GPU. The designed of stream processor unit has been carried out in Verilog on Altera Quartus II and simulated using ModelSim tools. The functionality of the modelled blocks is verified using test inputs in the simulator.The simulated execution time of 8-bit pipelined multiplier is 60 ps and 100 ns for 8-bit pipelined adder while operating at 90 MHz.